Bioluminescent optogenetic (BL-OG) activation of neurons during mouse postnatal brain development - Emmanuel L. Crespo; Mansi Prakash; Andreas Bjorefeldt; William E. Medendorp; Nathan C. Shaner; Diane Lipscombe; Christopher I. Moore; Ute Hochgeschwender (STAR Protocols, 2021)
Summary: Bioluminescent optogenetics (BL-OG) allows activation of photosensory proteins, such as opsins, by either fiberoptics or by administering a luciferin. BL-OG thus confers both optogenetic and chemogenetic access within the same genetically targeted neuron. This bimodality offers a powerful approach for non-invasive chemogenetic manipulation of neural activity during brain development and adult behaviors with standard optogenetic spatiotemporal precision. We detail protocols for bioluminescent stimulation of neurons in postnatally developing brain and its validation through bioluminescence imaging and electrophysiological recording in mice.For complete information on the use and execution of this protocol, please refer to Medendorp et al. (2021).